A novel platform for sharing and renting clothing to reduce environmental pollution - Todorovska, Ana; Trajanov, Dimitar; Gramatikov, Sasho; Krajchevska, Evgenija (Ss Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2020)
In today’s rapidly developing, technology driven world, the environment is being polluted in numerous ways, significantly more than in the past. Considering the fact that the fashion industry is the second largest polluter worldwide, it is evident that changes are needed in the way clothing is viewed and used. In this paper, we present a possible solution to this problem, which is built using the constantly advancing concept of shared economy. The platform we present is intended to create an online space that is used to share clothes that are not considered useful by their owners. Furthermore, the rental of expensive clothing for special occasions is provided. Adhering to the importance of the business aspect of any novelty being introduced, a market research was also conducted in our country. This paper includes these results, together with the conclusions drawn and the possible improvements suggested.
Keywords: Sharing economy platform, Sharing economy, Fashion, Pollution